2012
DOI: 10.1088/1478-3975/9/5/055005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurements and modeling of cargo–motor interactions during fast transport in the living axon

Abstract: The kinesins have long been known to drive microtubule-based transport of sub-cellular components, yet the mechanisms of their attachment to cargo remain a mystery. Several different cargo-receptors have been proposed based on their in vitro binding affinities to kinesin-1. Only two of these—phosphatidyl inositol, a negatively charged lipid, and the carboxyl terminus of the amyloid precursor protein (APP-C), a trans-membrane protein—have been reported to mediate motility in living systems. A major question is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In support of this model, rapid anterograde axonal transport of APP has been clearly demonstrated in cell culture (Koo et al, 1990; Seamster et al, 2012; Szpankowski et al, 2012). In contrast, several recent reports have shown that much of the holoprotein is actually processed into different fragments that are assorted to distinct transport vesicles before they exit the cell body (Muresan et al, 2009; Villegas et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…In support of this model, rapid anterograde axonal transport of APP has been clearly demonstrated in cell culture (Koo et al, 1990; Seamster et al, 2012; Szpankowski et al, 2012). In contrast, several recent reports have shown that much of the holoprotein is actually processed into different fragments that are assorted to distinct transport vesicles before they exit the cell body (Muresan et al, 2009; Villegas et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…All three KIF5s are expressed in brain, as well as at least two of the light chains, KLC1 and KLC2 (Rahman et al, 1998). Kinesin-1 has been implicated in transport of synaptic vesicles (Sato-Yoshitake et al, 1992), amyloid precursor protein (Kamal et al, 2001; Kamal et al, 2000; Satpute-Krishnan et al, 2006; Seamster et al, 2012), neurofilaments (Li et al, 2012; Xia et al, 2003), post-synaptic neurochemical receptors (Hirokawa et al, 2010), endoplasmic reticulum and Golgi membranes (Lippincott-Schwartz et al, 1995), and mitochondria (Campbell et al, 2014). Defects in kinesin-1 have been implicated in accelerating Alzheimer’s disease (Stokin et al, 2005), activation of axonal stress kinase with enhanced phosphorylation of tau (Falzone et al, 2010) and abnormal proteasome transport and distribution (Otero et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…121,247 Biophysical evidence indicated that 15aa of the C-terminus of APP was sufficient to promote the transport of APP in squid axons 122 and that APP beads had a high-binding affinity for kinesin-1. 123 In addition, genetic evidence showed that excess human APP or Drosophila APP-like (APPL) and the loss of function of Drosophila APPL resulted in phenotypes similar to motor protein mutants, indicating a function for APP in axonal transport. 124 Interestingly, the C-terminal deletions of human APP or APPL (including the kinesin-binding region) disrupted APP transport and failed to interact functionally with kinesin-1.…”
Section: App-cargo Complexmentioning
confidence: 99%